Využití finanční analýzy stavebního podniku pro potřeby řízení - Klosová, Sandra (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Tématem bakalářské práce je finanční analýza stavebního podniku pro potřeby řízení. Jejím cílem je posoudit finanční zdraví zvoleného stavebního podniku a popsat jejich využití pro management podniku. Práce se dělí na dvě části. Teoretická část popisuje metodický postup finanční analýzy a způsob jejího využití při řízení podniku. Praktická část se zabývá finanční analýzou společnosti STAVITELSTVÍ DANIEL STRYK s.r.o. v letech 2008 – 2011. Finanční analýza byla zpracována na základě elementárních metod, poměrových ukazatelů a vybraných souhrnných ukazatelů.

The topic of the bachelor thesis is the financial analysis of the construction company and its managerial impact. The main goal is to evaluate the financial stability of the subject and explain its utility for the company management. The thesis is divided into two main parts. The theoretical part describes the methodology of the financial analysis and the way to use the output for management purposes. In the practical part the financial analysis of the STAVITELSTVI DANIEL STRYK s. r. o. in 2008 – 2011 is being performed. The financial analysis is based on elementary methods, indexes, summative ratios and key performance indicators.
Utilization of Financial Analysis of Construction Company for Needs of Management
Keywords: Stavební podnik; finanční analýza; rozvaha; výkaz zisku a ztráty; Construction company; financial analysis; balance sheet; profit and loss statement; P/L